2021
DOI: 10.1186/s12893-021-01388-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and fixation of proximal humeral fracture with severe medial instability using a small locking plate

Abstract: Background Currently, the reduction and support of comminuted medial cortex of humeral fracture remains a challenge, Therefore, a novel reduction and fixation technique that employs an anteromedial small locking plate was explored in this study, and its viability and the associated complications were assessed. Methods Fifteen cases of proximal humeral fractures with medial instability (five cases were classified as three-part and ten as four-part b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In view of the high incidence of postoperative complications, some investigators have suggested that an adjuvant plate or fibular strutallograft (FSA) could be used for additional fixation in addition to PHILOS [ 20 , 21 ]. The plates can be placed in various positions, including the anterior and medial to the proximal humerus [ 6 , 22 ]. However, the technique of anterior plate assisted internal fixation has rarely been described, and few studies have been performed on the effect of lesser tuberosity fractures and their associated medial calcar disruption on patients with proximal humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the high incidence of postoperative complications, some investigators have suggested that an adjuvant plate or fibular strutallograft (FSA) could be used for additional fixation in addition to PHILOS [ 20 , 21 ]. The plates can be placed in various positions, including the anterior and medial to the proximal humerus [ 6 , 22 ]. However, the technique of anterior plate assisted internal fixation has rarely been described, and few studies have been performed on the effect of lesser tuberosity fractures and their associated medial calcar disruption on patients with proximal humerus fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have concluded that the integrity of the medial structure is closely related to postoperative complications. If the medial cortex cannot provide effective support during the operation, the medial column collapse will occur even with the fixation of the calcar screws [ 6 , 7 ]. The collapsed humeral head is associated with long-term postoperative pain and functional limitations of the shoulder joint.…”
Section: Introductionmentioning
confidence: 99%